CZYNNOŚCI SPRAWDZAJĄCE PROWADZONE W STOSUNKU DO OSOBY PODEJRZEWANEJ CHRONIONEJ IMMUNITETEM W POLSKIM PROCESIE KARNYM - Janusz, Barbara (Wydział Prawa i Administracji UAM, 2005)
The issues discussed in the paper relate to the checking proceedings carried out pursuant to article 307 of the code of penal proceedings in respect of a suspected person enjoying material, formal and jurisdictional immunity. The said article proposes a different, from the traditional one, typological approach to the immunity, taking into account a broader aspect of the code of penal proceedings. The checking proceedings are carried out before any preparatory proceedings take place; therefore, properly undertaken actions ensure efficiency of the whole course of proceedings and proper realisation of the basic principles of a criminal trial. They also serve as a guarantee of the competences of the participants to the criminal proceedings. According to article 307 of the code of criminal procedure, there are three possible ways of the checking procedure: a) request for complementary data (information) to the ones included in the information of the crime; b) addition of complementary data (information) contained in the information of a crime, consisting of the hearing of the party providing information in the capacity of a witness; c) checking the facts by the very organ itself, normally, by way of operational and investigation tasks. According to article 307 para. 5 of the code of penal procedure, it is possible to carry out checking procedures regarding the information possessed by the police, and regarding information or intelligence as to which a question might arise that a crime had been committed. Checking proceedings, i.e. a stage clearly separated from the preparatory proceedings, partially realises the objectives and tasks of the preparatory proceedings, which becomes especially pronounced and significant when data about people are being collected, as among those data there is also information about immunity which may have been granted to a given person at a certain time. There are two possible ways in which the checking procedure may be terminated; 1). by a decision not to instigate proceedings; or 2). by a decision to instigate proceedings. The following conclusions have been formulated: material immunities and jurisdictional immunities disclosed in the course of the checking proceedings result in automatic decisions to reject the application to instigate preparatory proceedings; 2). the disclosure, in the course of checking proceedings, of the formal immunity should result in an automatic instigation o f preparatory proceedings, which is related to the necessity to commence, by an authorised prosecutor, of an action to start a relevant procedure to procure the permission to enforce law. The above conclusions are subject to transformations under the public and private claims procedures.
CHECKING OF FACTS EXERCISED IN RESPECT OF A SUSPECTED PERSON ENJOYING IMMUNITY IN POLISH PENAL PROCEEDINGS